Mandat Yang Terlupakan: Mengaktivasi Kembali Otoritas Spiritual Jemaat Awam Dalam Pelayanan Pelepasan (Sebuah Kajian Teologis) - Haryo Kanigoro Arianto; Tricia Verina Saper (Jurnal Shema, 2026)
Deliverance ministry is a crucial dimension of the church's mission; however, in modern ecclesiastical praxis, this role is often narrowed into an exclusive ministry reserved for the clergy or individuals with specific spiritual gifts. This phenomenon has created a "forgotten mandate," where lay believers lose awareness of the spiritual authority they rightfully possess in Christ. This article aims to reconstruct the theological understanding of lay authority and propose the urgency of reactivating this mandate within deliverance ministry. Using a qualitative method with a theological-exegetical approach, this research dissects biblical foundations, such as the delegation of power to the disciples and the legal standing of believers in Christ's victory. The findings indicate that authority over the powers of darkness is not a prerogative of ecclesiastical office but rather an ontological identity of every believer (the priesthood of all believers). This study concludes that the church must undergo a reorientation of teaching to restore the spiritual confidence of the congregation. The activation of this authority must be integrated into Christ-centered discipleship, ensuring that lay believers are no longer passive objects but active agents of liberation in spiritual warfare..